The broad-lined Type-Ic supernova SN 2022xxf and its extraordinary two-humped light curves: I. Signatures of H/He-free interaction in the first four months - Kuncarayakti H.; Sollerman J.; Izzo L.; Maeda K.; Yang S.; Schulze S.; Angus C.R.; Aubert M.; Auchettl K.; Della Valle M.; Dessart L.; Hinds K.; et al. (EDP Sciences, 2025)
We report on our study of the supernova (SN) 2022xxf based on observations obtained during the first four months of its evolution. The light curves (LCs) display two humps of similar maximum brightness separated by 75 days, unprecedented for a broad-lined (BL) Type Ic supernova (SN IcBL). SN 2022xxf is the most nearby SN IcBL to date (in NGC 3705, z = 0.0037, at a distance of about 20 Mpc). Optical and near-infrared photometry and spectroscopy were used to identify the energy source powering the LC. Nearly 50 epochs of high signal-to-noise ratio spectroscopy were obtained within 130 days, comprising an unparalleled dataset for a SN IcBL, and one of the best-sampled SN datasets to date. The global spectral appearance and evolution of SN 2022xxf points to typical SN Ic/IcBL, with broad features (up to ~14 000 km s−1) and a gradual transition from the photospheric to the nebular phase. However, narrow emission lines (corresponding to ~ 1000–2500 km s−1) are present in the spectra from the time of the second rise, suggesting slower-moving circumstellar material (CSM). These lines are subtle, in comparison to the typical strong narrow lines of CSM-interacting SNe, for example, Type IIn, Ibn, and Icn, but some are readily noticeable at late times, such as in Mg I λ5170 and [O I] λ5577. Unusually, the near-infrared spectra show narrow line peaks in a number of features formed by ions of O and Mg. We infer the presence of CSM that is free of H and He. We propose that the radiative energy from the ejecta-CSM interaction is a plausible explanation for the second LC hump. This interaction scenario is supported by the color evolution, which progresses to blue as the light curve evolves along the second hump, and by the slow second rise and subsequent rapid LC drop. SN 2022xxf may be related to an emerging number of CSM-interacting SNe Ic, which show slow, peculiar LCs, blue colors, and subtle CSM interaction lines. The progenitor stars of these SNe likely experienced an episode of mass loss consisting of H/He-free material shortly prior to explosion.